UPAYA GURU BK DALAM MEMBENTUK KARAKTER SISWA DI SMP N 2 PAYAKUMBUH - Najla Hana Rifasya; Hidayani Syam; Syafrizal (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Character education is the main focus in forming a generation that has strong moral and ethical values. In the context of secondary education, the role of Guidance and Counseling (BK) teachers has important significance in shaping the character of junior high school students. This research aims to describe the role of guidance and counseling teachers in supporting the character formation of junior high school students. The guidance and counseling teacher not only functions as an academic advisor, but also as a facilitator in developing student character. They play a role in providing guidance and counseling that helps students identify desired values, understand the consequences of their behavior, and develop necessary social and emotional skills. Through a holistic approach, guidance and counseling teachers can design counseling programs that suit students' needs, provide support when facing conflicts or challenges, and facilitate extracurricular activities that strengthen character values. Apart from that, guidance and counseling teachers also collaborate with parents and other subject teachers to create a learning environment that supports character formation. In this research, we used observation, interviews and documentation analysis methods to gain a comprehensive understanding of the role of guidance and counseling teachers in forming character. junior high school students. The research results show that guidance and counseling teachers have a positive impact in shaping students' character through counseling interventions, counseling and self-development activities. It is hoped that this research can contribute to further understanding of the important role of guidance and counseling teachers in character education at the secondary level. The practical implications of this research can be used as a basis for increasing the role of guidance and counseling teachers in supporting the character formation of junior high school students, so that they can become individuals with integrity, responsibility, and able to contribute positively to society.